Pengaruh Budaya Organisasi t erhadap Kinerja Karyawan p ada Hotel Royal n' Lounge Jember - Rahma Azizah Azizah; Sutrisno Sutrisno; Sri Wahyuni (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract The purpose of this research was to analyze the influence of organizational culture on employee performance at Royal n' Lounge Hotel Jember. The population in this research was all operational employees of Royal n' Lounge Hotel Jember in total of 47 respondents. The research results showed that the artifacts and creations, values, and basic assumptions significantly affected employee performance at Royal n' Lounge Hotel Jember with the positive direction. Suggestions in this research are: 1) hotel management is expected to further develop and provide knowledge about the organizational culture to the employees, in hope that this can improve employee performance at Royal n' Lounge Hotel Jember; 2) it is expected that furthe r research provides development in goal orientation in the research and the addition of respondents, so the research hopefully achieves better results. Keywords : Organizational Culture, Performance